Hakikat Otonomi Daerah Yang Luas, Nyata Dan Bertanggung Jawab Dalam Perspektif Utilitarianisme - Cynthia Hadita; Susi Dwi Harijanti (Riau Law Journal, 2022)
The problem that arises because the regions do not have absolute independence to take care of their own household affairs can be one of the factors that hinder Indonesia from becoming a welfare state through the progress of the regions. The problem of the essence of regional autonomy at the level of implementation of its system in the frame of the Unitary State of the Republic of Indonesia is still not in accordance with the nature of broad, real, and responsible regional autonomy so that this will also hinder the achievement of the greatest happines of the greatest number for as in the theory of utilitarianism in achieving the goal of the state to become a welfare state ). The research method used is normative juridical by taking a historical approach and legislation. The results showed that the urgency of implementing broad, real, and responsible regional autonomy is needed in the regional government system in order to meet regional needs with the essence of autonomy possessed in order to realize the greatest happiness of the regional community.